Microstructure and mechanical behavior of an annealed automatic gas tungsten arc weld joint of TA16 and TC4 titanium alloys. (6th February 2019) - Shao, Ling; Wu, Sujun; Peng, Wenya; Datye, Amit; Liu, Jingbei; Lefoul, Marc Antoine; Ju, Hongbo; Liu, Ying
Abstract: The joining of TA16 (Ti-2Al-2.5Zr, wt%) and TC4 (Ti-6Al-4V, wt%) titanium alloys was carried out using an automatic gas tungsten arc welding technique. The microstructures of different zones in the annealed weld joints were investigated, and the mechanical properties of the annealed weld joints were assessed using microhardness, uniaxial tensile and fracture toughness tests. An asymmetrical hardness profile across the annealed weld joint was obtained in the dissimilar titanium alloys weld joint with a higher hardness value in the heat-affected zone of TC4 side. The fracture location of welded tensile specimens was always at the heat-affected zone of TA16 side. Test results showed that the fracture toughness of the heat-affected zone of TA16 side was the highest, that of TC4 base material was the lowest, and the fracture toughness of other zones were as follows: TA16 base material > fusion zone > heat-affected zone of TC4 side. Scanning electron microscope examinations were performed on the fracture surface in order to identify the relevant fracture mechanisms of different zones in the annealed weld joint.